4.0k views
4 votes
Evaluate the function f(a)=2a^2 +a if f(-a)

1 Answer

4 votes
to get the answer simply substitute the given value to the given equation

after substituting the value, instead of f(a) it will then become f(-a)

change the value of every "a" in the equation according to the given; which is -a.

after substituting the given the answer will become f(-a) = -2a^2 - a

solution:

f(a) = 2a^2 + a if f(-a)

f(-a) = 2(-a)^2 +(-a)

f(-a) = -2a^2 - a from addition the operation became subtraction because in math (+)(-) = (-) "positive time negative is negative".


User JakeP
by
6.5k points